O ensino fundamental de nove anos no Estado de Alagoas: um estudo da efetivação da política de implantação a partir da experiência do Município de Delmiro Gouveia - AL - Rocha, Idnelma Lima da (2012)
This study is an investigation into the policy implementation of fundamental education for 09 years in municipal and state schools of the State of Alagoas, from the experience of the city of Delmiro Gouveia, in order to analyze how this policy was instituted and changes that have caused the daily life of schools. To account for this purpose, we reflect on the historical and legal precepts that guided the policy of expansion of fundamental education to nine years; understand the guidelines that underpin this policy at the federal, state and municipal levels, analyze the political and pedagogical directions the educational system of the State of Alagoas and the municipality of Gouveia Delmiro on the fundamental education of nine years, and identifying the changes caused by the deployment in the school routine and school assessment that actors make this policy of expansion of more than one year, from empirical research in the field. As a foundation for the analysis of educational policy, the theoretical approach is guided in studies on educational policy, universal fundamental education and quality of education and academic research on the subject in other states. As a methodological framework, we adopted the ways of qualitative research, structured document analysis of the propositions in the official documents of the three bodies around the school and field research using semi-structured interviews with school stakeholders - teachers and parents - who live directly with students and children the consequences of change. The data after the Crusaders, were grouped considering the research objectives, thus making the analytical framework in terms of actions undertaken to implement the policy at school, the operation and effectiveness of the proposal, and the weights of teachers and parents about the deployment fundamental School for nine years. The survey results show that the implementation provided in the public schools of Delmiro plus lighter, dismissed the participation of the school community, both in preliminary discussions regarding the preparation for understanding and involvement with the conclusion; has demonstrated inconsistencies between the proposal and practice regarding changes and adjustments of all orders, has generated dissatisfaction and discontent in the vertical format that was established and the lack of teaching aids and material that has compromised their results, which to date have been inexpressible.